Frequency of juxtapapillary diverticulum detected during endoscopic retrograde cholangiopancreatography - Castillo Arrieta, Yhonny (2025)
Introduction: The weakest part of the duodenal wall is the ampulla of Vater, since here the circular arrangement of the duodenal musculature is destructured to integrate the sphincter of Oddi. This characteristic could be the reason why most duodenal diverticula appear in the juxtapapillary region, even including the papilla inside. Objective: The objective of the research was to determine the patients diagnosed with juxtapapillary diverticulum (JD) after endoscopic retrograde cholangiopancreatography (ERCP), who were confused with different previous diagnoses. Materials and methods: Retrospective study with intentional sample, where ERCP was performed on a universe of 12,686 patients who were referred with different previous gastrointestinal pathologies, therefore, they required diagnosis or treatment with this procedure. Results: Of the 12,686 patients who underwent ERCP, between 01/07/2014 and 28/06/2024, a total of 872 (6.9%) presented a confirmatory diagnosis of juxtapapillary diverticulum, a diagnosis that differed partially or totally from the one presented before the procedure. Conclusions: The prevalence detected was one of the highest reported for Latin America. DY is generally asymptomatic, affecting mostly elderly patients, but when it is symptomatic, they present different signs and symptoms, which simulate a wide variety of diagnoses, where the clinical and previous imaging studies do not provide sufficient clues for a correct analysis, therefore, ERCP is the perfect tool for the timely diagnosis and treatment of DY, clearing previous diagnostic doubts.